Coherence Analysis of Reading Texts in English Textbooks for Class X SMA "Work in Progress" Published by Ministry of Education and Culture of the Republic of Indonesia - Chindy Yulia Permatasari; Safnil Arsyad (Journal of English for Specific Purposes in Indonesia (JESPI), 2023)
In teaching English at school, the teacher uses textbooks as reference material and carries out the process of learning English. Textbooks have an essential role in getting information and knowledge. Thus, text can be good when the text has coherence. When the text is coherent, it will make it easier for students to understand the text. This research aimed to determine the type and level of coherence used in reading texts in the book 'Work in Progress' for class X high school students Published by KEMENDIKBUD in 2022. This research used a quantitative approach. Based on the results of analysis that have been carried out by researchers on 11 reading texts consisting of five categories of Descriptive Text, Recount Text, Procedure Text, Expository Text, and Narrative Text in the textbook. The results of this research all the texts are coherent or good because the level of coherence in the texts is good, with the level percentage of coherence being 80%. The texts from the book that have been analyzed are included in good textbooks because the percentage of the highest overall coherence level is at a good and sufficient level. The components of coherence included in the text are keyword repetition, consistent pronouns, transition signals, and logical ordering. The most dominant text coherence is Narrative Text (48%) with getting fair score. Regarding the coherence analysis results, the research suggests that teachers can choose this book as a handbook for teaching English to their students.